INFECTION OF BACTERIAL AEROMONAS SP. ON KOI FISH DURING QUARANTINE PERIOD - Manika Putri, Anak Agung Sagung Rani; Mahatmi, Hapsari; Besung, I Nengah Kerta (Buletin Veteriner Udayana, 2022)
Bacteria Aeromonas sp . is one type of pathogenic bacteria in humans and can cause disease in animals. These bacteria also attack various species of freshwater fish, one of which is the koi fish. The purpose of this study was to obtain preliminary data on the infection ofbacteria Aeromonas sp. in koi fish ( Cyprinus carpio L), which has the potential to cause disease in koi fish in Bali, especially koi fish that have just been imported from outside the island of Bali during the quarantine period. A total of 19 koi fish measuring 15-25 cm are suspected of being infected with bacterial diseases and dead koi fish swab was done on the scales and gills, then the sample was isolated and identified bacteria at the Balai Besar Veteriner. Water temperature and pH are measured to determine water quality. The data obtained are presented descriptively. The results showed that one sample (5.26%) was infected with Aeromonas sp.